The role of cow dung and kitchen manure composts and their non-aerated compost teas in reducing the incidence of foliar diseases of Lycopersicon esculentum (Mill) (International Journal of Agricultural Research, Innovation and Technology, 2014)
Compost teas are fermented watery extracts of composted materials used for their beneficial effect on plants. A study was conducted in the field to compare the efficacy of cow dung and kitchen manure composts and their derived non-aerated compost teas on disease symptoms expression and severity of Lycopersicon esculentum. The experimental layout was a complete randomised block design comprising six treatments, each of which was repeated three times: the negative control plot (Tm-); the positive control or fungicide plot (Tm+); the cow dung compost plot (Cpi); the kitchen manure compost plot (Cpii); the compost tea derived cow dung plot (Tci); and the compost tea derived kitchen manure plot (Tcii). Compost tea derived cow dung was revealed to be richer in elemental nutrients (N, P, K) than compost tea from kitchen manure, and significantly (p < 0.0001) enhanced fruit yield per plant. Similarly, the two composts and their derived compost teas significantly (p < 0.0001) reduced the incidence and severity of disease symptoms compared to the controls, with the highest efficacy accounting for cow dung compost and compost tea. Although the non-aerated compost teas were not amended with micro-organisms, these results suggest that the two compost teas in use were rich enough in microbial pathogen antagonists, and therefore, are perceived as potential alternatives to synthetic chemical fungicides. Future work will attempt to identify these microbial antagonists with highly suppressive activity in the non-aerated compost teas. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21100 Int. J. Agril. Res. Innov. & Tech. 4 (1): 88-97, June, 2014